2020
DOI: 10.1111/pcmr.12880
|View full text |Cite
|
Sign up to set email alerts
|

Emerging strategies to treat rare and intractable subtypes of melanoma

Abstract: The melanoma field represents a paradigm for preclinical and clinical advancements in targeted and immune therapy modalities, with 13 new FDA-approved therapies since 2011 (Dummer et al., 2018a, 2018b; Long et al., 2018; Ribas & Flaherty, 2011). The catalyst for the development of targeted therapy modalities was the identification of activating NRAS mutations and BRAF mutations in 1984 (Albino,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 136 publications
(200 reference statements)
0
28
0
Order By: Relevance
“…Furthermore, nearly 90% of NRAS missense mutations occur at codon 61 in CM, compared to 54% for MM. The remaining 46% of mutations are located at codon 12 and codon 13 ( 91 ). Compared with NRAS activating mutations at positions 12 and 13, NRAS Q61 mutations exert a stronger activating effect on the MAPK pathway since codon 61 is the catalytic residue for GTP hydrolysis and Q61 mutation impedes the return of RAS to an inactive GDP-bound state ( 92 ).…”
Section: Mutations and Signaling Pathway Dependency In MMmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, nearly 90% of NRAS missense mutations occur at codon 61 in CM, compared to 54% for MM. The remaining 46% of mutations are located at codon 12 and codon 13 ( 91 ). Compared with NRAS activating mutations at positions 12 and 13, NRAS Q61 mutations exert a stronger activating effect on the MAPK pathway since codon 61 is the catalytic residue for GTP hydrolysis and Q61 mutation impedes the return of RAS to an inactive GDP-bound state ( 92 ).…”
Section: Mutations and Signaling Pathway Dependency In MMmentioning
confidence: 99%
“…The activity of BRAF kinase is regulated by the interaction formed between A-loop and P-loop, thus mutations in either A-loop or P-loop disrupt the interaction and cause hyperactivation of the kinase ( 93 , 95 ). In CM, more than 90% of mutations are present on the V600 codon, whereas in MM only 63% are V600 mutations, with the remainder (37%) on the G469, D594, and K601 codons ( 91 , 93 ). In other words, MM not only has far less frequent BRAF missense mutations but also has more diverse locations for BRAF mutations as compared to CM.…”
Section: Mutations and Signaling Pathway Dependency In MMmentioning
confidence: 99%
“…These figures are increasing and is expected to continue growing worldwide [ 2 ] as a consequence essentially of excessive exposure to sunlight related to leisure, which undoubtedly will increase the health investment dedicated to the diagnosis and treatment of this tumor [ 3 ]. It should be also highlighted that some less frequent subtypes of melanomas—i.e., acral, uveal, and mucous melanomas—are responsible for significant morbidity associated with metastasis, responding typically worse to newer therapies [ 4 ]. Although the use of advanced therapies based on new drugs approved by the FDA have been applied to treatment since 2011 [ 5 ], all of the aforementioned advises the development of extensive research, which provides enough scientific evidence especially on new therapeutic targets, with the aim of developing new drugs specifically aimed toward these new targets that can improve patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…I want to congratulate the authors for this fruitful article and make some contributions.In the study, it has been indicated that the immunotherapy era was significantly added benefits to overall survival (OS) for melanoma patients; however, the rare sites of melanoma should be included in these two contemporary groups. Unluckily, the patients with these relatively rare melanoma subtypes (acral lentiginous, uveal, and mucosal melanomas) which typically do not respond to the emerging immunotherapy that has been approved for the more common type of melanoma, and thus have worse overall survival rates [2] and attempting to reach enduring safe and effective responses in these high-risk subtypes of melanoma is one of the field's main challenges [3].We searched for the distant rare subtypes of melanoma (Stage -6th edition.…”
mentioning
confidence: 99%
“…We strongly highlight effective clinical and preclinical studies toward these rare subtypes of melanoma, including the combination of immunotherapy and anti-vascular agents (NCT03955354, NCT03991975, NCT03602547), new immune checkpoint inhibitors (NCT02071940 with an anti-CSF1) and cell-based approaches (NCT01983748) [ 3 , 4 ].…”
mentioning
confidence: 99%